A Case Report and Review of the Literature: Infectious Aneurysm Formation in the Pulmonary Arteries—A Rare but Perilous Sequela of Persisting Infection With Klebsiella pneumoniae - Ruwisch, Jannik; Fischer, Bettina; Häbel, Lea; Laenger, Florian; Bollmann, Benjamin-Alexander (Frontiers in Microbiology, 2022)
Septic aneurysms of the pulmonary artery are rare conditions, with few cases having been reported worldwide. They are assumed to result from septic emboli that cause a local inflammatory reaction of the arterial wall, ultimately leading to degenerative changes. We report the case of a 63-year-old female patient presenting with Klebsiella pneumoniae urosepsis and first diagnosis of diabetes mellitus, who developed a life-threatening infectious pulmonary artery aneurysm secondary to bacteremia with Klebsiella pneumoniae. The patient required a lobectomy due to pulmonary hemorrhage. We review the clinical hallmarks of Klebsiella pneumoniae related septic pulmonary embolic disease and summarize currently known risk factors for the development of infectious aneurysmatic disease including diabetes mellitus and other states of immunosuppression. The featured case aims to increase the awareness for this seldom but life-threatening complication of infectious diseases such as Klebsiella pneumoniae urosepsis.